HUBUNGAN SIKAP BELAJAR DENGAN HASIL BELAJAR MATEMATIKA SISWA PADA MATERI PECAHAN KELAS V SDN 10 SINGKAWANG - Elna Malini; Abd. Basith; Insan Suwanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Based on a research problem at SDN 10 Singkawang, the mathematics learning outcomes of grade V students from the final mathematics score data are known that 72% of student scores are still in the range of KKTP, namely 65. Based on the results of interviews with class V teachers who stated that students felt bored during mathematics learning, students were only enthusiastic about learning when the subject matter they liked, and students did not pay attention to the teacher when explaining. This study aims to determine the significance of the relationship between learning attitudes and students' mathematics learning outcomes in grade V fraction material of SDN 10 Singkawang. This research method is a correlation research with a quantitative approach. The population in this study is all grade V students of SDN 10 Singkawang. The sampling technique in this study is a saturated sampling technique. The results of the study showed that: 1) the learning attitude of grade V students at SDN 10 Singkawang was at a high criterion with an overall average of 84.14. 2) The learning outcomes of grade V students at SDN 10 Singkawang are at the criteria of sufficiency with an overall average of 66.88. 3) There was no significant relationship between learning attitudes and mathematics learning outcomes of grade V students at SDN 10 Singkawang.